2019
DOI: 10.1002/jcb.28999
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq analysis of potential lncRNAs and genes for the anti‐renal fibrotic effect of norcantharidin

Abstract: Background As a common phenotype in chronic kidney disease, renal interstitial fibrosis has been largely studied. Norcantharidin (NCTD), a derivative of naturally occurring cantharidin, has an anti‐renal fibrotic effect. However, its underlying mechanisms of the protective role remain largely unknown. Long noncoding RNAs (lncRNAs) play vital parts in tissue homeostasis modulation under pathophysiological conditions. In this study, we discovered the underlying lncRNAs and genes, which may contribute to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Norcantharidin is a widely used agent in cancer chemotherapy (Deng & Tang, 2011). Our previous studies showed that NCTD suppressed RIF both in vitro and in vivo renal fibrosis models (Li, Chen, Liu, Peng, Hou, et al, 2011; Li, Chen, Liu, Peng, Wang, et al, 2011; Li et al., 2012, 2013; Liu et al., 2008; Xiao et al., 2019). Here, we found that TGF‐β1‐induced Fn expression was abrogated by NCTD in HK‐2 cells, which was in agreement with previous studies and provide further evidence for the anti‐fibrotic effect of NCTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norcantharidin is a widely used agent in cancer chemotherapy (Deng & Tang, 2011). Our previous studies showed that NCTD suppressed RIF both in vitro and in vivo renal fibrosis models (Li, Chen, Liu, Peng, Hou, et al, 2011; Li, Chen, Liu, Peng, Wang, et al, 2011; Li et al., 2012, 2013; Liu et al., 2008; Xiao et al., 2019). Here, we found that TGF‐β1‐induced Fn expression was abrogated by NCTD in HK‐2 cells, which was in agreement with previous studies and provide further evidence for the anti‐fibrotic effect of NCTD.…”
Section: Discussionmentioning
confidence: 99%
“…NCTD is widely used in the treatment of liver and stomach cancers and other gastrointestinal tumors (Deng & Tang, 2011). In previous studies, we showed that NCTD effectively suppressed RIF (Li, Chen, Liu, Peng, Hou, et al, 2011; Li, Chen, Liu, Peng, Wang, et al, 2011; Liu et al., 2008; Xiao et al., 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Studies have found that lncRNA is involved in many life activities such as the dose compensation effect, and it has become a hot topic in genetic research [30][31][32]. Many studies have reported that lncRNA is involved in regulating the progression of malignant tumours [33].…”
Section: Discussionmentioning
confidence: 99%
“…Additional urine analysis reported upregulation of 625 lncRNAs and downregulation of 177 lncRNAs, some of which (NONRATT044682, 361619 and 689064) could be possible biomarkers of renal fibrosis. In another study, lncRNAs Gm10251, Fam120aos and Gm16076 regulated the Jak/STAT pathway, whereas lncRNAs Fam12aos and Gm16076 interacted with fibroblast integrin beta1 (ITGB1) [ 64 ]. The lncRNA 74.1 was downregulated in HK-2 cells exposed to TGF-β.…”
Section: Role Of Lncrnas In Renal Diseasesmentioning
confidence: 99%